Analisis Validitas Modul IPA Berbasis Etno-STEM Untuk Meningkatkan kemampuan Berpikir Tingkat Tinggi Siswa - Sasti Handayani Wakhidyah; Joko Waluyo; Pramudya Dwi Aristya Putra (Jayapangus Press, 2026)
Validity testing is required to produce standardised learning modules. This study aims to analyse the validity of Ethno-STEM-based science learning modules to enhance students’ higher-order thinking skills. This study serves as the initial stage in the development of Ethno-STEM modules, which act as a prerequisite for the implementation of HOTS-based learning. The 4D model was used for module development. Data was collected using validity instruments and subsequently analysed descriptively. The module validity instrument comprises several assessment aspects, namely the assessment of content (substance) and media (construct), which cover ethnoscience and STEM along with their design. The research subjects were three expert lecturers in Science Education and one secondary school teacher. The assessment results were then calculated using Aiken’s V formula. The validity results indicate that the Ethno-STEM-based Science learning module meets the ‘highly valid’ category, both in terms of content (content) with an average score of 0.908333 from expert validators and media (construct) validators with an average score of 0.88889, as well as from user validators who achieved an average score of 0.9. The Etno-STEM-based Science Learning Module is deemed valid for enhancing students’ higher-order thinking skills.